Potential for enhancement of enzymatic hydrolysis of sugar maple (Acer saccharum) - Uygut, Muhammet Ali; Corbett, Derek; Wood, Christopher; Zelie, Matt; Bujanovic, Biljana (My University, 2015)
Electron beam (EB), irradiation and hot-water extraction (HWE) of wood have been used independently as pretreatment methods to improve enzymatic hydrolysis (EH) of hardwoods by reducing cellulose crystallinity and removing most of xylans, respectively. Moreover, the results of our previous studies have demonstrated that after acetone:water (9:1) (AW) washing, the lignin content in HW-extracted wood decreased while hydrolysability increased. In this study the potential to increase accessibility of sugar maple (Acer saccharum) for EH was further explored by performing EB irradiation (bars; 250, 750 and 1000 kGy) followed by HWE (chips; 160 °C, 2 hours) and/or AW (chips; 120 °C, 20 min). After pretreatments (EB, HWE, EB_AW, EB_HWE, HWE_AW, EB_HWE_AW), wood was grounded to 30 mesh and EH was performed (Cellic ® CTec2, HTec2, Novozymes; 72 hours). Samples of hydrolysates collected throughout EH (sampling every 4 hour in duplicates) were analyzed for the concentration of glucose and xylose while the wood before and after EH was analyzed for the content of lignin and glucose and xylose-based polysaccharides. These studies are expected to enhance pretreatment procedure for the production of glucose from hardwoods by applying relatively mild and environmentally friendly procedure
Diğer - Poster
Keywords: Enzymatic hydrolysis; Sugar maple; Electron beam; Irradiation; Hot-water extraction